Scaling Up Private Sector Participation in Road Asset Management in Sub-Saharan Africa - World Bank (World Bank, Washington, DC, 2022)
The purpose of this study is to evaluate non-traditional means to raise additional private financing for the upgrade and maintenance of developing countries’ road networks. To achieve this goal, it combines an in-depth review of Sub-Saharan Africa (SSA) countries’ road funds’ (RF) performance and road public private partnerships (PPPs) to evaluate the potential for RFs to fund road PPPs when specific conditions are met. This report presents to explore how, in few selected cases, SSA RFs can be reformed to substantially increase the amount of public and private monies flowing towards the maintenance and or upgrade of the core road networks of SSA countries.